KAJIAN KUALITAS DAN HASIL PENGOLAHAN BIODIESEL NYAMPLUNG (Colophyllum inophyllum) PADA VARIASI METODE EKSTRAKSI, METODE DEGUMMING DAN KONSENTRASI METANOL - Anif, Muhammad Umar (Universitas Jenderal Soedirman, 2012)
SUMMARYNyamplung is a multy-function plant. Beside its wood is good forconstruction and furniture material, the almond is used for bio-diesel fuel´smaterial. The advantage in using Nyamplung as bio-diesel fuel´s material is theproductivity which may reach until 10 tons/hectare. Besides, Nyamplung has highendurance of environment, big amount of population, longer range of lifespan (1to 50 years), year-round productivity, especially during September to November.Nyamplung´s oil content may reach around 40% to 70%. Nyamplung´s oil is notused as food product (non edible). Thus, this plant will not disturb the foodstability program.This research was aimed to observe the extraction method, methanolconcentration, and the best Degumming method to produce Nyamplung´s biodiesel oil. So that Nyamplung may be considered as the alternative fuel to replacethe ordinary fuel which is continually decreased nowdays.This research was conducted at Agriculture Product ProcessingTechnology Laboratory and Agriculture Technic Laboratory of JenderalSoedirman University in Purwokerto, Quality control Laboratory of SMKN 1temanggung and PT Pertamina RU IV Cilacap, during May 2009 until October2009. The research was used Complete Randomized Block Design that consistedof three factors, namely: Extraction Method, Degumming Method and MethanolConcentration which was needed on Transeserification reaction. Observedvariables were Chemical composition of Nyamplung Biodiesel variable andbiodiesel´s performance to diesel engine as the Physical Variable.Based on the research, it was resulted the best treatment for Nyamplung´sseed extraction was Chemical method extraction. The greatest result ofdegumming method was reached by using 1% Sulfuric Acid (H3PO4) and 5%methanol concentration. In such a state, pH balance value was 6.58, viscocity oilas 5.645 cst, Flash Point was 157.295C, free fatty acid was 1.1%, acid numberwas 0.1, Iodine number was 82.775% and Alcyl Ester number was 93.545%.Based on visual observation, Nyamplung´s biodiesel oil has clear browncolor. The smell was similar like fresh oil. The stationere was 10 minute remindsstable. The soot produced was thin as it was resulted from perfect combustion.Key words: Nyamplung, bio diesel , extraction method, Degumming Method,Methanol Concentration, Transeserification reaction, biodiesel´s performance.